Implementación de un dispositivo para la gestión de los recursos del ancho de banda (2006)
ABSTRACT: The apogee of the communications at world-wide level causes that the organizations are seen in the necessity to use tools like Internet and the internal networks of computers (LAN: local area networks), assuming these like a fundamental requirement for the improvement of their processes and the fulfilment of their objectives. As a result of this necessity, almost all the companies of our means have in their physical installations a computer science system supported by networks of computers with Internet connection. Because all the employees have access to Internet with the same rights, it does not matter if a user is making an inadequate use of the bandwidth which the company has, because this user will always have the same priority that another user who is making use of some application or service of Internet considered critical for the operation of the company. This problem is originated due to the lack of bandwidth management. In order to solve this problem, a device that is in charge to manage the resources of the bandwidth of a network with connection to Internet was developed.